Stratifying sudden death risk in adults with drug‐resistant focal epilepsy: The SUDEP‐CARE score. (27th September 2022) - Serrand, Chris; Rheims, Sylvain; Faucanié, Marie; Crespel, Arielle; Dinkelacker, Vera; Szurhaj, William; Biraben, Arnaud; Bartolomei, Fabrice; de Grissac, Nathalie; Landré, Elizabeth; Denuelle, Marie; Vercueil, Laurent; et al.
Abstract: Background and purpose: A clinical risk score for sudden unexpected death in epilepsy (SUDEP) in patients with drug‐resistant focal epilepsy could help improve prevention. Methods: A case–control study was conducted including (i) definite or probable SUDEP cases collected by the French National Sentinel Mortality Epilepsy Network and (ii) control patients from the French national research database of epilepsy monitoring units. Patients with drug‐resistant focal epilepsy were eligible. Multiple logistic regressions were performed. After sensitivity analysis and internal validation, a simplified risk score was developed from the selected variables. Results: Sixty‐two SUDEP cases and 620 controls were included. Of 21 potential predictors explored, seven were ultimately selected, including generalized seizure frequency (>1/month vs. <1/year: adjusted odds ratio [AOR] 2.6, 95% confidence interval [CI] 1.25–5.41), nocturnal or sleep‐related seizures (AOR 4.49, 95% CI 2.68–7.53), current or past depression (AOR 2.0, 95% CI 1.19–3.34) or the ability to alert someone of an oncoming seizure (AOR 0.57, 95% CI 0.33–0.98). After internal validation, a clinically usable score ranging from −1 to 8 was developed, with high discrimination capabilities (area under the receiver operating curve 0.85, 95% CI 0.80–0.90). The threshold of 3 has good sensitivity (82.3%, 95% CI 72.7–91.8), whilst keeping a good specificity (82.7%, 95% CI 79.8–85.7). Conclusions: These results outline the importance of generalized and nocturnal seizures on the occurrence of SUDEP, and show a protective role in the ability to alert someone of an oncoming seizure. The SUDEP‐CARE score is promising and will need external validation. Further work, including paraclinical explorations, could improve this risk score. Abstract : The SUDEP‐CARE score was developed to target the most at‐risk patients who suffer from drug‐resistant focal epilepsy. The higher the score is, the more is the risk of a sudden unexpected death in epilepsy event.